The Longtime Behavior of an SIR Epidemic Model with Free Boundaries (Journal of Nonlinear Modeling and Analysis, 2024)
In [6] , the authors studied an SIR epidemic model with free boundary. They first proved the global existence and uniqueness of solution, and thengave the criteria for spreading and vanishing. They also obtained the longtime behavior for the case of vanishing. However, the longtime behavior whenspreading happens remains open. In this short paper, we aim to solve thisopen problem.